Industrial work practice, discipline, and vocational interest on motorcycle engineering students’ work readiness - Rian Mahesa; Hasan Maksum; Wagino Wagino; Heri Prabowo (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
This study aimed to examine the influence of Industrial Work Practice, Discipline, and Vocational Interest on students’ work readiness in the Motorcycle Engineering Department at SMK Negeri 2 Palembang. This research employed a quantitative correlational design involving 72 twelfth-grade students selected using saturated sampling. Data were collected through Likert-scale questionnaires and analyzed using descriptive statistics, Pearson correlation, simple regression, and multiple linear regression with IBM SPSS 25. The results showed that Industrial Work Practice had a positive and significant effect on work readiness (R² = 0.171; p < 0.05), Discipline demonstrated the strongest influence (R² = 0.390; p < 0.05), and Vocational Interest also significantly affected work readiness (R² = 0.122; p < 0.05). Simultaneously, the three variables contributed 59.2% to students’ work readiness. These findings indicate that practical industrial experience, strong discipline, and vocational interest are important factors in improving vocational students’ readiness to enter the workforce.